2016
DOI: 10.1002/ird.2029
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Options for the Sustainable Use of Agricultural Drainage Water For Irrigation in Egypt by Simulation Modelling

Abstract: The water management simulation model DRAINMOD-S was applied to simulate different strategies for using agricultural drainage water for irrigation over a 20-year period. The irrigation strategies considered were: (i) fresh/non-saline water as the baseline for comparison; (ii) drainage water of different salinities; (iii) cyclic use of fresh water and drainage water; (iv) deficit irrigation combined with controlled drainage; and (v) interseasonal cyclic use of drainage water and fresh water (2 years drainage/2y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…Reclaiming saline soil and maintaining landscaping plants require massive freshwater resources and the viable water source needs to be considered in the context of freshwater resources competition between agricultural demand and markedly increasing other demands, such as domestic and industrial water uses in coastal regions. The use of unconventional water resources, including saline water, has been intensively studied for agricultural and landscaping purposes (Qadir & Oster, 2004; Shalhevet, 1994; Wahba, 2017). It has been shown the advantages of using drip irrigation under saline conditions with soil matric potential controlling in the root zone (Kang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Reclaiming saline soil and maintaining landscaping plants require massive freshwater resources and the viable water source needs to be considered in the context of freshwater resources competition between agricultural demand and markedly increasing other demands, such as domestic and industrial water uses in coastal regions. The use of unconventional water resources, including saline water, has been intensively studied for agricultural and landscaping purposes (Qadir & Oster, 2004; Shalhevet, 1994; Wahba, 2017). It has been shown the advantages of using drip irrigation under saline conditions with soil matric potential controlling in the root zone (Kang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The study simulated the fluctuations in groundwater level fairly precisely but did not simulate drainage outflow as precisely. Later, a different version of the DRAINMOD model was used by Wahba (2017) to simulate various alternatives for the application of drainage effluent for irrigation in north‐west Egypt.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, different management strategies must be developed for an appropriate sustainable use of these resources (soil, water and crop) under the existing challenges. The study of Wahba () showed that the cycle between fresh and drainage water can be done successfully if fresh water is available in the early crop establishment stages. The cycling between fresh and drainage water interseasonally also appears to be feasible and all these strategies must be tested in pilots before large application.…”
Section: Resultsmentioning
confidence: 99%